Late accretion offers pathway to misaligned disk around the planet-hosting IRAS 04125+2902 - Hühn, León-Alexander; Jiang, H.-C.; Dullemond, Cornelis (Astronomy and astrophysics, 2025)
We present a 3D hydrodynamical simulation of the accretion of a gas cloudlet onto the IRAS 04125+2902 binary system, where the 3-Myr-old primary hosts a transiting planet. We demonstrate that such an accretion event can naturally produce a circumstellar disk that is misaligned with respect to the rest of the system, consistent with the observed misaligned transition disk. In the model, the prescribed orbital plane of the cloudlet is largely retained by the resulting circumstellar disk after undergoing gravitational interactions with the secondary during the initial accretion. After ∼4.4 binary orbits, a disk with Rd = 300 AU has formed around the stellar primary made of ∼13% of the cloudlet mass, Md,p = 2.1 × 10−3 M . The companion also retains some of the cloudlet’s mass and forms a disk with Md,c = 9.3 × 10−5 M , though only the transition disk around the primary has been observed. Our findings highlight the importance of considering mass inflow onto a protoplanetary disk for its evolution.